2017
DOI: 10.1016/j.athoracsur.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of the David V Valve-Sparing Root Replacement Compared With Bioprosthetic Valve-Conduits for Aortic Root Aneurysms

Abstract: VSRR and BIO result in equivalent operative mortality and morbidity with similar midterm survival and valve durability. VSRR is an effective alternative to BIO for aortic root pathologic conditions; however, careful patient selection is paramount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Yacoub et al 4 reported 7 (5.83%) perioperative strokes. David et al 13 15 reported 7 thromboembolic events in their first report, although the rate of stroke in the most recent study from David technique was only 3.3%. At least two other studies with the David procedure had only one postoperative stroke.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Yacoub et al 4 reported 7 (5.83%) perioperative strokes. David et al 13 15 reported 7 thromboembolic events in their first report, although the rate of stroke in the most recent study from David technique was only 3.3%. At least two other studies with the David procedure had only one postoperative stroke.…”
Section: Discussionmentioning
confidence: 97%
“…13 14 A recent report from Emory on the David procedure had a higher operative mortality at 5.7%. 15 However, Ouzounian et al 2 recently updated the Toronto experience with an in-hospital mortality (0.4%). The low rate of early mortality in their study is maybe related to less concomitant cardiac surgery, exclusion of nonelective patients, and a younger patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increasing number of high volume cardiac surgery centers recommend aortic valve sparing surgery in the light of improved hemodynamic profile, 69 similar short-to midterm and improved long-term mortality and morbidity. [70][71][72] In a large single center cohort, BAV patients that had undergone either aortic valve replacement or ascending aorta replacement had no root dilatation at midterm follow-up of 8.1 § 5.4 years, negating the need for prophylactic aortic root replacement in these cases. 73…”
Section: Aortic Root and Ascending Aorta Surgerymentioning
confidence: 99%
“…For some young patients, the aortic cusps are nearly normal anatomically and morphologically, aortic valve-sparing root replacement was also an effective alternative (Ouzounian et al, 2016). In contrast, recent study provided that valve-sparing root replacement and bio-composite valve led to equivalent operative mortality and morbidity with similar midterm survival and valve durability (Esaki et al, 2017). In emergency situation, aortic valve replacement could be performed to AD patients (Erbel et al, 2014a,b).…”
Section: Aortic Aneurysm and Dissection: Need More Predictors And Timmentioning
confidence: 99%